1988
DOI: 10.1073/pnas.85.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric prostaglandin F2 compounds arising from prostaglandin D2: a family of icosanoids produced in vivo in humans.

Abstract: Prostaglandin (PG) D2 has been shown to be transformed by human 11-ketoreductase to 9a,11f-PGF2, a biologically active metabolite that is produced in vivo. During the course of developing a mass spectrometric assay for 9a,113-PGF2, several compounds with characteristics similar to PGF2 were detected in both plasma and urine of normal humans by selected ion monitoring. Analysis of pooled plasma obtained from patients with mastocytosis during severe episodes of systemic mast cell activation associated with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In 1988, Wendelborn et al [19] reported that healthy subjects exhibited 48-460 pg/ml of urinary PGF 2 -like compounds. The corresponding levels for circulating PGF 2 -like compounds was in the range 1-12 pg/ml.…”
Section: Historic Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…In 1988, Wendelborn et al [19] reported that healthy subjects exhibited 48-460 pg/ml of urinary PGF 2 -like compounds. The corresponding levels for circulating PGF 2 -like compounds was in the range 1-12 pg/ml.…”
Section: Historic Backgroundmentioning
confidence: 98%
“…Total lipid extracts from plasma and urine from the above-mentioned samples were therefore treated with n-butylboronic acid. n-Butylboronic acid forms The determination of prostaglandin metabolites in human urine [16] 1988 Discovery of PGF 2 isomers derived from PGD 2 metabolism in human plasma and urine [19] 1990…”
Section: Historic Backgroundmentioning
confidence: 99%
“…In aqueous solutions, however, PGD 2 in an unstable compound that undergoes isomerization of the lower side chain and these isomers can likewise be reduced by 11-ketoreductase to yield isomers of 9α,11β-PGF 2 [12]. In studies undertaken to further characterize these compounds utilizing a gas chromatographic (GC)/mass spectrometric (MS) assay, we found that in plasma samples from normal volunteers that were processed and analyzed immediately, a series of peaks were detected possessing characteristics of F-ring PGs (Fig.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In aqueous solutions, however, PGD 2 is an unstable compound that undergoes isomerization of the lower side chain and these isomers can also be reduced by 11-ketoreductase to yield isomers of 9α,11β-PGF 2 α [4]. In studies undertaken to further characterize these compounds utilizing mass spectrometry, it was found that when plasma samples from normal volunteers were processed and analyzed immediately, a series of peaks were detected possessing characteristics of F-ring PGs.…”
Section: Historical Perspectivementioning
confidence: 99%